Endoscopic Transcervical Catheterization in the Domestic Cat. Issue 1 (31st October 2014) - Zambelli, D; Bini, C; Cunto, M
Contents Feline‐assisted reproduction is still not routinely performed in veterinary practice, although there is an increasing interest on the subject by cat breeders. In recent years, many techniques for artificial insemination in the domestic cat have been developed with regard to the intrauterine deposition of sperm through the catheterization of the cervix. Transcervical catheterization has been described also for diagnostic and therapeutic purposes. This article provides the first description of a new method for cervical catheterization, under the direct visualization of the cervix, using a rigid endoscope and a new specially designed transcervical catheter. The procedure was performed on 14 queens with a success rate of 85.71%.